KONSEP ORWELISASI DAN PARKINSONISASI DALAM SISTEM PEMERINTAHAN PUBLIK - Yeni Sri Lestari (Jurnal Public Policy, 2017)
This article discusses the importance of the role of the right government system within a country. One of the determinants of the good governance system is based on the accuracy in the selection of government bureaucracy system. Therefore, to provide a more detailed understanding, this article will discuss about the bureaucratic system. This review will examine two bureaucratic systems currently dominantly applied by most countries in the world, namely Orwell Bureaucracy (Orwellization) and Parkinson's Bureaucracy (Parkinsonization). This article is divided into four studies, first on the backgrounds of Orwell and Parkinson, the two studies on the concept of Orwellization and Parkinsonization framework, the three analyzing the application of both concepts within a country, and the fourth is criticism given by experts to the concept of Orwellization and Parkinsonization. In this study it is found that the concept of Orwellization and Parkinsonization is still relevant in studying the problems of bureaucratic systems in some countries, the concept of Orwellisasi can create a strong state but weaken the issue of Human Rights (HAM), while the concept of Parkinsonization contributed considerably in the development effort but weaken the system of recruitment of public officials. However, there are some experts who give criticism to the concept of  ureaucracy Orwellisasi and Parkinsonisasi this, this is not apart from weakness owned by each bureaucracy concept. Keywords: bureaucracy, Orwellisasi, dan Parkinsonisasi